Współpraca przygraniczna w dobie wyzwań polityki strukturalnej Unii Europejskiej 2007-2013 = Borderland cooperation in the age of the challenges of the EU`s structural policy 2007-2013 - Sługocki, Waldemar (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Borderland cooperation is an essential element not only in building positive relations between Polish and German people, but it also constitutes an important factor in the European integration process. It is a foundation which allows implementing many joint undertakings whose aim is social and economic development of the Polish-German borderland.
Keywords: współpraca polsko-niemiecka; pogranicze polsko-niemieckie; Unia Europejska; polityka strukturalna